Correlates of Parental Dysfunctionality and Depressive Disorder among Adolescents in Bungoma County, Kenya (Impact: Journal of Transformation, 2022)
Physical and psychological well-being of family members is significantly determined by family functioning and its impairment affects the family. Since there is a bidirectional process between parents and their offspring, parental dysfunctionality has a negative impact on adolescents’ mental health. This study therefore sought to examine the correlates of parental dysfunctionality and depressive disorder among adolescents in Bungoma County, Kenya. From the total sample size of 368 respondents, 338 subjects constituting 91.7% response rate participated in the study. The composition of the 338 participants included 169 parents and 169 adolescents where 121, 71.6% were female and 48, 28.4% male adolescents with the mean age 16.8 ± (SD: 1.704). Frequency of female parents/guardians was also higher 101, (59.8%) as opposed to their male counterparts (68, 40.2%). The parents/guardians’ mean age was 44.0 ± (SD: 11.74) accordingly. Parental dysfunctionality was assessed in terms of parental Intimate Partner Violence (IPV), parental alcohol use and parental depressive disorder (DD). Results from this study indicated that 63.3% of the parents and guardians reported experiencing some form of IPV with the most prevalent form of IPV being psychological abuse at 56.8%, followed by emotional abuse at 34.9%, physical abuse at 32.5% and sexual violence at 21.3%. Whereas the prevalence of alcohol use disorder was at 4.8% and alcohol dependency was at 3.6%. The prevalence of depressive disorder among parents was at 49.1%, and among the adolescents at 67.5%. Pearson correlation test was used to test the correlation between the two variables. The result showed a positive and significant relationship between parental DD scores and presence of IPV (r = .499, p < .001). However, there was no significant correlation between the parental dysfunctionality markers and adolescent DD (p > 0.05). This shows parental dysfunctionality does not relate to adolescent DD. This present study concluded that parents/guardians’ DD was associated with higher chances of IPV.